2019
DOI: 10.1177/0271678x19857818
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of brain damage after traumatic brain injury by pharmacological enhancement of KCNQ (Kv7, “M-type”) K+ currents in neurons

Abstract: Nearly three million people in the USA suffer traumatic brain injury (TBI) yearly; however, there are no pre- or post-TBI treatment options available. KCNQ2-5 voltage-gated K+ channels underlie the neuronal “M current”, which plays a dominant role in the regulation of neuronal excitability. Our strategy towards prevention of TBI-induced brain damage is predicated on the suggested hyper-excitability of neurons induced by TBIs, and the decrease in neuronal excitation upon pharmacological augmentation of M/KCNQ K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 129 publications
(201 reference statements)
2
36
0
Order By: Relevance
“…Using in situ hybridization, we confirmed that KCNQ2 transcription was increased after hyperexcitability challenge to the brain; however, KCNQ3 transcription was not altered. This is consistent with our previous finding of lack of KCNQ3 transcription in the cortex after TBI, despite increases to KCNQ2 (Vigil et al, ). As KCNQ3 is abundantly co‐assembled with KCNQ2 in neurons, any specified role of KCNQ3 plasticity in neuromodulation of hippocampus has yet to be revealed (Soh et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Using in situ hybridization, we confirmed that KCNQ2 transcription was increased after hyperexcitability challenge to the brain; however, KCNQ3 transcription was not altered. This is consistent with our previous finding of lack of KCNQ3 transcription in the cortex after TBI, despite increases to KCNQ2 (Vigil et al, ). As KCNQ3 is abundantly co‐assembled with KCNQ2 in neurons, any specified role of KCNQ3 plasticity in neuromodulation of hippocampus has yet to be revealed (Soh et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Specifically, upregulation of KCNQ2 expression can only occur in neurons that survive a deleterious insult that induces excitotoxicity, represented here by the stark contrast of signal between the types of principal neurons. We recently report a similar result concerning cortical neuron plasticity in responding to and surviving an adverse insult (Vigil et al, ).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations